2003
DOI: 10.21061/jcte.v20i1.625
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Teacher Efficacy Related to Career Commitment of Novice Agriculture Teachers

Abstract: This exploratory descriptive study investigated the differences between teacher efficacy of novice teachers based on relatively low and high levels of career commitment. The population was 91 novice teachers in their first, second, and third years of teaching in agricultural education in Ohio. The teachers were split into two groups based on their median scores of career commitment. Although the two groups had the same teacher efficacy at the beginning of the school year, teachers with higher career commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
(43 reference statements)
0
30
0
Order By: Relevance
“…Student teachers who planned to pursue a teaching career in public education were more efficacious than their peers who did plan to become an agriculture teacher (Harms & Knobloch, 2005). Moreover, novice teachers with higher career commitment were more efficacious after the first 10 weeks of the school year compared to their peers with lower career commitment (Knobloch & Whittington, 2003). Although some of this research has resulted in predicting students' career interests, goals, persistence, and performance (Lent et al, 2005), there remains a need to study generalized perceived self-efficacy in general, and agricultural science majors in particular because of the shortage of human capital in the agricultural disciplines.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Student teachers who planned to pursue a teaching career in public education were more efficacious than their peers who did plan to become an agriculture teacher (Harms & Knobloch, 2005). Moreover, novice teachers with higher career commitment were more efficacious after the first 10 weeks of the school year compared to their peers with lower career commitment (Knobloch & Whittington, 2003). Although some of this research has resulted in predicting students' career interests, goals, persistence, and performance (Lent et al, 2005), there remains a need to study generalized perceived self-efficacy in general, and agricultural science majors in particular because of the shortage of human capital in the agricultural disciplines.…”
Section: Theoretical Frameworkmentioning
confidence: 94%
“…Each teacher explained the reasons they chose teaching as their profession. The writers found that the teachers really do love their job, it can be seen from their commitment and experience in holding the job as argued by Knobloch and Whittington (2003) that career commitment is a factor that is related to teacher selfefficacy of the teaching experience. The three teachers each viewed their job as a very honourable profession, they are each very grateful to be a teacher because this profession has been their (individual) dream since they were in senior high school.…”
Section: Teaching Careermentioning
confidence: 99%
“…The enthusiasm of teachers has been discussed as one of the most important factors in producing excellence in the teaching and learning process (Lan, 1995;Mortimor, 1999;Knobloch & Whittington, 2003). The importance of enthusiasm will lead a teacher to produce a higher performance in their teaching.…”
Section: Teachers' Enthusiasmmentioning
confidence: 99%
“…Experiential learning is a "framework for examining and strengthening the critical linkages among education, work, and personal development" (Kolb, 1984, p. 4) and can be characterized as both a process and context (Roberts, 2006). In synthesizing experiential learning theory, Knobloch (2003) identified the four tenets of experiential learning as learning by doing, learning through real-life contexts, learning through projects, and learning through problem-solving.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Self-confidence and personal satisfaction has been show to impact teaching of beginning agriculture teachers (Joerger & Boettcher, 2000). Knobloch and Whittington (2003) found pre-service and novice teachers possessing a greater commitment to their careers were more efficacious after applied teaching experiences in the classroom. More specifically, early teaching experiences may determine commitment to the teaching profession and contributes to helping students learn and develop (Knobloch & Whittington, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%